Analysis of N6-Methyladenosine Methylation Modification in Fructose-Induced Non-Alcoholic Fatty Liver Disease - Luo, Yunchen; Zhang, Zhijian; Xiang, Liping; Zhou, Bing; Wang, Xuejiao; Lin, Yi; Ding, Xiaoying; Liu, Fang; Lu, Yan; Peng, Yongde (Frontiers in Endocrinology, 2021)
Improvements in living standards have led to non-alcoholic fatty liver disease (NAFLD), one of the most common chronic liver diseases worldwide. Recent studies have shown that N6-methyladenosine (m6A), a type of RNA modification, is strongly associated with many important biological processes. However, the relationship between m6A methylation modifications and NAFLD remains poorly understood. In the present study, through methylated RNA immunoprecipitation sequencing and RNA transcriptome sequencing in high fructose diet-induced NAFLD mice, we found that hypermethylation-encoding genes were mainly enriched in lipid metabolism processes. We identified 266 overlapping and differentially expressed genes (DEGs) that changed at both the mRNA expression level and m6A modification level. Among them, 193 genes displayed increased expression and m6A modification, indicating that m6A RNA modifications tend to be positively correlated with NAFLD. We further compared the high fructose diet-induced NAFLD mouse model with leptin receptor-deficient mice and found that DEGs enriched in the lipid metabolism pathway were up-regulated in both groups. In contrast, DEGs associated with the immune inflammatory response were up-regulated in the high fructose diet group, but down-regulated in leptin receptor-deficient mice. Taken together, our results demonstrate that m6A methylation modifications may play an important role in the development of NAFLD.